O regime de tributação sobre os lucros auferidos no exterior por intermédio de controladas e seus efeitos: operações de inversão corporativa - Brandão, Ana Gabriela Guilherme Marques (2021)
This thesis aims to examine the main points of the Brazilian legislation about the taxation on profits earned through foreign subsidiaries and its possible effects on the decision making of multinationals established in the country, with regard to the international restructuring of their operations. The experience of the United States, in the last three decades, shows that the corporate invertion has become a very attractive option for American multinationals, in the corporate reorganization of the economic group itself or through a business combination with other foreign companies. In corporate inversion, the corporate structure of a multinational group is changed and a foreign company, typically located in a low tax country, becomes the parent company of the economic group. In other words, the inverted company becomes controlled by the new foreign parent company. Since the Brazilian government taxes, annually, on an accrual basis, the profits earned by direct and indirect subsidiaries abroad, regardless of the nature of the income or whether it is a subsidiary located in a tax haven, subject to a privileged tax regime or under-taxation, corporate inversion appears as an option to Brazilian multinationals with high level of internationalisation. Law 12.973/14 brought some measures that may mitigate the impact of these rules, such as the possibility of consolidating, in Brazil, the results of the operations abroad, the deferral of payment of taxes on profits abroad and the possibility of taking advantage of the presumed 9% credit in relation to profits of subsidiaries that operate in certain activities. However, such regimes will apply until 2022. In view of this, this thesis aims to present a comparison between the rules of tax transparency adopted by the Brazilian legislation and by other countries, mainly the United States, considering that the phenomenon that occurred in that country may gain space in Brazil. Once the corporate inversion may bring tax savings, the work will highlight, in the light of current doctrine and jurisprudence on tax planning, in which terms transactions of this nature would be opposed to the Tax Authorities and will also provide recommendations and suggestions on the procedures to be observed in the implementation of these structures in order to mitigate the tax risks.